Respuesta :

[tex]sin^{-1}(x) + cos^{-1}(-\frac{1}{2}) = \pi[/tex]
[tex]sin[(sin^{-1}(x) + cos^{-1}(-\frac{1}{2})] = 0[/tex]
[tex]sin(sin^{-1}(x)) \cdot cos(cos^{-1}(-\frac{1}{2})) + cos(sin^{-1}(x)) \cdot sin(cos^{-1}(-\frac{1}{2})) = 0[/tex]

[tex]-\frac{x}{2} + \sqrt{1 - x^{2}} \cdot \sqrt{1 - (-\frac{1}{2})^{2}} = 0[/tex]
[tex]\sqrt{1 - x^{2}} \cdot \sqrt{1 - (\frac{1}{4})} = \frac{x}{2}[/tex]
[tex]\sqrt{1 - x^{2}} \cdot \sqrt{\frac{3}{4}} = \frac{x}{2}[/tex]

[tex]\frac{\sqrt{3(1 - x^{2})}}{2} = \frac{x}{2}[/tex]
[tex]\sqrt{3(1 - x^{2})} = x[/tex]
[tex]3(1 - x^{2}) = x^{2}[/tex]
[tex]3 - 3x^{2} = x^{2}[/tex]
[tex]4x^{2} = 3[/tex]

[tex]x^{2} = \frac{3}{4}[/tex]
[tex]x = \pm \frac{\sqrt{3}}{2}[/tex]

Substitute both x-values in, and only [tex]x = \frac{\sqrt{3}}{2}[/tex] works.

Thus, [tex]x = \frac{\sqrt{3}}{2}[/tex] is your solution.
ACCESS MORE